Measurement of protein and albumin/globulin ratio in patients infected with visceral leishmaniasis - Ekhlass Noori Ali (College of Pharmacy / Mustansiriyah University, 2013)
The study included 30 serum samples from people (age: 1-12 years) suffering from visceral leishmaniasis (Leishmania donovani) infection, which were collected from the Central Health Laboratories, and a similar number of healthy controls. The serum level of total protein, albumin and globulin was measured, and fractions of globulin (alpha 1 globulin, alpha 2 globulin, beta globulin, gamma globulin) were also analyzed. The results showed a significant increase (P ≤ 0.05) in total protein of patients (82.27 vs. 57.75 g/L), as compared with controls, while there was a non-significant decrease in the level of albumin (30.63 vs. 31.66 g/L). A similar significant increased level of globulin was also observed in patients (51.63 vs. 24.83 g/L), and the fractions of globulin (alpha 1 globulin, alpha 2 globulin, beta globulin, gamma globulin) were similarly increased (6.01, 13.20, 10.37, 21.64 vs. 3.74, 6.63, 7.06, 7.50 g/L, respectively). Accordingly, the albumin:globulin ratio was decreased in patients as compared with controls (0.62 vs. 1.20).